Validation of Palliative peRInatal Multi-domain Assessment (PRIMA) Questionnaire (Paliativní medicína, 2024)
Perinatal palliative care is based on the cooperation of multiple workers with multiple areas of expertise. Perceptions and understanding of the possibilities and current tools of specialised palliative care vary between specialties and between professionals. The necessary validated questionnaire, which would map the perception of individual health professionals in the Czech and international environment, is still missing. The Palliative peRInatal Multidomain Assessment (PRIMA) questionnaire is presented and externally validated in a two-round process. Internal consistency is calculated (Cronbach’s α for the whole questionnaire, for the subset of items about the actual state, and the subset of items about the ideal state is 0.799 [95% confidence interval 0.550–0.878], 0.767 [0.544–0.877], and 0.867 [0.763–0.916] respectively).
Keywords: perinatal palliative care; multidisciplinarity; domains of palliative care; external validation; internal consistency